Lethal intent [large type] - Putman, Cara C. (Center Point Large Print, 2021)
"Caroline Bragg's life has never been better. She and Brandon Lancaster are taking their relationship to the next level, and she has a new dream job as legal counsel for Praecursoria - a research lab that is making waves with its cutting-edge genetic therapies. The company's leukemia treatments even promise to save desperately sick kids - kids like eleven-year-old Bethany, a critically ill foster child at Brandon's foster home. When Caroline's enthusiastic boss wants to enroll Bethany in experimental trials prematurely, Caroline objects, putting her at odds with her colleagues. They claim the only goal at Praecursoria is to save lives. But does someone have another agenda? Brandon faces his own crisis. As laws governing foster homes shift, he's on the brink of losing the group home he's worked so hard to build. When Caroline learns he's a Praecursoria investor, it becomes legally impossible to confide in him. Will the secrets she keeps become a wedge that separates them forever? And can she save Bethany from the very treatments designed to heal her?"--